Patients' subjective concepts about primary healthcare utilisation: the study protocol of a qualitative comparative study between Norway and Germany. Issue 6 (13th June 2013) - Herrmann, Wolfram J; Haarmann, Alexander; Flick, Uwe; Bærheim, Anders; Lichte, Thomas; Herrmann, Markus
Abstract : Background: In Germany, utilisation of ambulatory healthcare services is high compared with other countries: While a study based on the process data of German statutory health insurances showed an average of 17.1 physician-patient-contacts per year, the comparable figure for Norway is about five. The usual models of healthcare utilisation, such as Rosenstock's Health Belief Model and Andersen's Behavioural Model, cannot explain these differences adequately. Organisational factors of the healthcare system, such as gatekeeping, do not explain the magnitude of the differences. Our hypothesis is that patients' subjective concepts about primary healthcare utilisation play a major role in explaining different healthcare utilisation behaviour in different countries. Hence, the aim of this study is to explore these subjective concepts comparatively, between Germany and Norway. Methods/design: With that aim in mind, we chose a comparative qualitative study design. In Norway and Germany, we are going to interview 20 patients each with qualitative episodic interviews. In addition, we are going to conduct participant observation in four German and four Norwegian primary care practices. The data will be analysed by thematic coding. Using selected categories, we are going to conduct comparative case and group analyses. Ethics and dissemination: The study adheres to the Declaration of Helsinki. All interviewees will sign informed consent forms and all patients will be observed during consultation. Strict rules for data security will apply. Developed theory and policy implications are going to be disseminated by a workshop, presentations for experts and laypersons and publications.